The Perils of Tax Smoothing : Sustainable Fiscal Policy with Random Shocks to Permanent Output - Tanner, Evan (IMF Working Papers; Working Paper ;, 2005)
If permanent output is uncertain, tax smoothing can be perilous: both debt levels and tax rates are difficult to stabilize and may drift upwards. One practical remedy would be to target the debt. However, our simulations confirm that such a policy would require undesirably volatile fiscal adjustments and may inhibit countercyclical borrowing. An alternative would be to link the primary surplus not only to the debt ratio (like tax smoothing) but also to its volatility, thus preempting further adjustments while gradually reducing the debt.